Adobe in design CC 2018 release: Classroom in a book/ Kelly kordes Anton & Tina Dejarld - Anton Kordes Kelly; Tina Dejarld (London: Pearson education limited, 2021)
Features Acrobat exchange software, PDF writer driver, Distiller software, capture plug-in, catalog software, type manager software, Acrobat Reader with and without Acrobat search, 14 type one fonts, PDF clip art, and an on-line electronic publishing guide.
The official training workbook form Adobe
Keywords: Text processing (Computer science); Portable document software